Enteroscopy-assisted ERCP in patients with surgically altered anatomy: Multicenter prospective registry (SAMISEN-B) using motorized spiral enteroscopy - Moreels, Tom G; Aabakken, Lars; Arvanitakis, Marianna; Knabe, Mate; Beyna, Torsten (Endoscopy International Open, 2024)
Background and study aims This was a prospective study of efficacy and safety of motorized spiral enteroscopy (MSE) to perform biliary endoscopic retrograde cholangiopancreatography (ERCP) in patients with surgically altered anatomy at five European centers.Patients and methods Consecutive patients with biliary indications for enteroscopy-assisted ERCP were enrolled. Objectives were technical success, adverse event (AE) rate, and patient radiation exposure.Results Eighty-nine patients were enrolled and one was excluded for a pancreatic indication. All participants had variations of Billroth II reconstruction (29.5%) or Roux-en-Y reconstruction (70.5%), either with naive papilla (39%) or hepaticojejunostomy (61%). Main indications were anastomotic stricture treatment and/or biliary stone removal. Enteroscopy to reach the bile duct was possible in 65 of 88 patients (74%), bile duct cannulation in 54 of 88 (61%), and therapeutic ERCP was technically successful in 48 of 88 (54%). In Billroth II variations, technical success was achieved in 13 of 26 patients (50%) compared with 35 of 62 (57%, P = 0.5792 Chi square) in Roux-en-Y reconstructions (including bariatric gastric bypass). ERCP with intact papilla was successful in 17 of 34 patients (50%) compared with 31 of 54 (57%, P = 0.4968 Chi square) in hepaticojejunostomy. The study was prematurely terminated July 2023 because MSE was withdrawn by the manufacturer for safety issues. Overall, in 12 of 88 patients (14%), AEs were recorded and six (7%) were considered serious. Only one serious AE was attributable to MSE enteroscopy: perforation of the proximal esophagus during enteroscope insertion.Conclusions This prospective multicenter study was prematurely discontinued due to withdrawal of the MSE by the manufacturer because of safety issues. Technical success of MSE-assisted biliary ERCP in different types of surgically altered anatomy was 54%, which was lower than anticipated. There was one esophageal perforation attributable to use of MSE. (clinicaltrials.gov: NCT05129449)
Keywords: Endoscopy Small Bowel; Small bowel endoscopy; Pancreatobiliary (ERCP/PTCD); GI surgery